Copulation Song in Drosophila: Do Females Sing to Change Male Ejaculate Allocation and Incite Postcopulatory Mate Choice? - Kerwin, P.; Philipsborn, A.C. (BioEssays, 2020)
Drosophila males sing a courtship song to achieve copulations with females. Females were recently found to sing a distinct song during copulation, which depends on male seminal fluid transfer and delays female remating. Here, it is hypothesized that female copulation song is a signal directed at the copulating male and changes ejaculate allocation. This may alter female remating and sperm usage, and thereby affect postcopulatory mate choice. Mechanisms of how female copulation song is elicited, how males respond to copulation song, and how remating is modulated, are considered. The potential adaptive value of female signaling during copulation is discussed with reference to vertebrate copulation calls and their proposed function in eliciting mate guarding. Female copulation song may be widespread within the Drosophila genus. This newly discovered behavior opens many interesting avenues for future research, including investigation of how sexually dimorphic neuronal circuits mediate communication between nervous system and reproductive organs.